2022
DOI: 10.3390/cells11121877
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Expression and Subcellular Distribution of eEF1A1 and eEF1A2 mRNAs during Neurodevelopment

Abstract: Neurodevelopment is accompanied by a precise change in the expression of the translation elongation factor 1A variants from eEF1A1 to eEF1A2. These are paralogue genes that encode 92% identical proteins in mammals. The switch in the expression of eEF1A variants has been well studied in mouse motor neurons, which solely express eEF1A2 by four weeks of postnatal development. However, changes in the subcellular localization of eEF1A variants during neurodevelopment have not been studied in detail in other neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…3G ). To differentiate regulated from a random coexistence of two mRNAs, we randomly simulated the position of Hsp90aa , Hsp90ab , or Hsp110 mRNAs over the dendritic shaft using a new module in ARLIN ( 88 ). ARLIN binned the dendritic shaft into 25 μm segments and organized them depending on their distance from the soma to consider changes in the number of HSP mRNAs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3G ). To differentiate regulated from a random coexistence of two mRNAs, we randomly simulated the position of Hsp90aa , Hsp90ab , or Hsp110 mRNAs over the dendritic shaft using a new module in ARLIN ( 88 ). ARLIN binned the dendritic shaft into 25 μm segments and organized them depending on their distance from the soma to consider changes in the number of HSP mRNAs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because dendritic spines have high levels of localized translation and protein concentration, we proposed they would require more HSPs to prevent aberrant interactions among unfolded proteins. Thus, we used ARLIN to analyzed stress-induced changes in the contiguity between HSP mRNAs, detected by smFISH, and the postsynaptic density, labeled by IF with PSD95 antibody ( 88 ) ( Fig. 3H ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although proteins can be directly targeted to specific subcellular locations by virtue of specific motifs, protein localisation in neurons is frequently controlled by targeting of the cognate mRNA, which is then translated locally, and this seems the most likely mechanism here. Indeed, a number of studies of both the mRNA content and translatome of axons have identified eEF1A1 but not eEF1A2 in axons of mice and rats (Taylor et al, 2009;Gumy et al, 2011;Shigeoka et al, 2016;Nijssen et al, 2018) and in dendrites, albeit in cultured cells (Wefers et al, 2022); other studies using TRAP and Riboseq methodology have shown enrichment of eEF1A1 in axons relative to cell bodies (Ostroff et al, 2019;Glock et al, 2021;Jung et al, 2023). It seems likely that there are one or more RNA binding proteins controlling the developmental switch resulting in the transport and subsequent translation of eEF1A1 in axons; the UTRs of eEF1A1 and eEF1A2, unlike the coding regions, are largely dissimilar (41% identity in 3'UTRs compared with 80% in the coding regions).…”
Section: Discussionmentioning
confidence: 99%
“…See Wefers et al . for detailed methods [28]. Separate analysis of somal cytoplasm and dendritic projections was carried out using the FISH-Quant polygon tool to outline regions of interest.…”
Section: Methodsmentioning
confidence: 99%